Pengaruh Bimbingan Klasikal dengan Media Leaflet Untuk Meningkatkan Pengetahuan tentang Bahaya Kecanduan Game online pada Siswa SMA Negeri 12 Pekanbaru - Hariani, Lafiza Suci; Syafriafdi, Non; Arlizon, R. (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine whether classical guidance services with leaflet media have an effect on increasing knowledge about the dangers of online game addiction in high school students. This study is a quantitative study. using an experimental method with a one-group pre-test-post-test design, with a one-subject group design. The data collection was carried out by distributing student knowledge tests about the dangers of online game addiction which were then analyzed using the Wilcoxon test with the help of the SPSS Version 27 program. This study shows that there are differences in the level of student knowledge about the dangers of online game addiction before and after the implementation of classical guidance. Then there is the influence of classical guidance services with leaflet media which is in the moderate category through the N-Gain test.